N-Doped porous carbon nanosheets decorated with graphitized carbon layer encapsulated Co9S8 nanoparticles: an efficient bifunctional electrocatalyst for the OER and ORR. Issue 3 (9th November 2018) - Li, Linghui; Song, Li; Guo, Hu; Xia, Wei; Jiang, Cheng; Gao, Bin; Wu, Chao; Wang, Tao; He, Jianping
Abstract : Graphitized carbon layer encapsulated Co9 S8 nanoparticles embedded into N-doped porous carbon nanosheets show an excellent bifunctional electrocatalytic performance for the OER and ORR. Abstract : Electrocatalysts with highly effective activity for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are considered to be the key factor of renewable energy technologies. Herein, we designed and synthesized bi-functional electrocatalyst Co9 S8 /C nanosheets (NSs) by reducing the Co3 O4 /C NS precursor with sodium sulfide. From the structural characterization, Co9 S8 is anchored on the graphitized carbon NSs homogeneously. According to the electrochemical measurements, the Co9 S8 /C NSs show excellent electrocatalytic activity towards both the ORR ( E onset = 0.892 V vs. RHE and E 1/2 is 0.778 V vs. RHE) and OER ( E onset = 1.50 V vs. RHE and the overpotential is 0.434 V vs. RHE at 10 mA cm −2 ) in 0.1 M KOH solution. In the ORR, Co9 S8 /C catalyzes through a 4-electron process like the commercial Pt-based catalyst. In addition, the Co9 S8 /C NSs show great long-term stability. The Co9 S8 /C NSs show excellent catalytic performance due to the rich active sites and two-dimensional sheet structure. The developed strategy offers an effective method for preparing bi-functional electrocatalysts for both the OER and ORR.